2022
DOI: 10.1101/2022.02.03.478927
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pax6 Limits the Competence of Developing Cerebral Cortical Cells

Abstract: The development of stable specialized cell types in multicellular organisms relies on mechanisms controlling inductive intercellular signals and the competence of cells to respond to such signals. In developing cerebral cortex, progenitors generate only glutamatergic excitatory neurons despite being exposed to signals with the potential to initiate the production of other neuronal types, suggesting that their competence is limited. Here we tested the hypothesis that this limitation is due to their expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 199 publications
(282 reference statements)
0
3
0
Order By: Relevance
“…Interestingly, we saw a much larger variation in the amount of Tuj1+ neurons produced in Pax6 -/organoids than in controls. One possible explanation for this is that Pax6 acts to protect cells from the influence of signalling molecules in the extracellular environment as has recently been shown in mice (Manuel et al, 2022). It is possible that the variation in the extent of precocious neural differentiation in Pax6 -/organoids is due to variability in the presence of environmental signals that promote cell cycle exit.…”
Section: Discussionmentioning
confidence: 94%
“…Interestingly, we saw a much larger variation in the amount of Tuj1+ neurons produced in Pax6 -/organoids than in controls. One possible explanation for this is that Pax6 acts to protect cells from the influence of signalling molecules in the extracellular environment as has recently been shown in mice (Manuel et al, 2022). It is possible that the variation in the extent of precocious neural differentiation in Pax6 -/organoids is due to variability in the presence of environmental signals that promote cell cycle exit.…”
Section: Discussionmentioning
confidence: 94%
“…A mathematical analysis of gene regulatory networks using Boolean and computational models has revealed an underpinning expression gradient in the mammalian cortex [ 65 , 66 ]. Although upstream secretary molecules that can induce the expression of Pax6 have not been identified yet, it is of interest that Pax6 controls the responsiveness to secreted molecules such as sonic hedgehog and BMP in the cortex [ 67 ]. Future analyses may reveal more about the relationship between Pax6 and secreted molecules.…”
Section: Pax6 In Cortical Patterningmentioning
confidence: 99%
“…In this section, we have discussed that Pax6 and its downstream transcriptional factors and signaling molecules are important for neural fate determination, where these transcriptional factors have stage- and cell type-specific regulatory mechanisms. A recent preprint article has reported that a conditional knock-out of Pax6 ectopically induces GABAergic interneurons, as well as oligodendrocyte precursor cells in the cortex [ 67 ]. This might be reasonable because cyclin D2 is upregulated in the Sey/Sey mouse cortex ([ 94 , 134 ] and our unpublished data).…”
Section: Pax6 In Neurogenesismentioning
confidence: 99%